Co‐designing an intervention to improve the process of deprescribing for older people living with frailty in the United Kingdom. (24th November 2022) - Silcock, Jonathan; Marques, Iuri; Olaniyan, Janice; Raynor, David K.; Baxter, Helen; Gray, Nicky; Zaidi, Syed T. R.; Peat, George; Fylan, Beth; Breen, Liz; Benn, Jonathan; Alldred, David P.
Abstract: Background: In older people living with frailty, polypharmacy can lead to preventable harm like adverse drug reactions and hospitalization. Deprescribing is a strategy to reduce problematic polypharmacy. All stakeholders should be actively involved in developing a person‐centred deprescribing process that involves shared decision‐making. Objective: To co‐design an intervention, supported by a logic model, to increase the engagement of older people living with frailty in the process of deprescribing. Design: Experience‐based co‐design is an approach to service improvement, which uses service users and providers to identify problems and design solutions. This was used to create a person‐centred intervention with the potential to improve the quality and outcomes of the deprescribing process. A 'trigger film' showing older people talking about their healthcare experiences was created and facilitated discussions about current problems in the deprescribing process. Problems were then prioritized and appropriate solutions were developed. The review located the solutions in the context of current processes and procedures. An ideal care pathway and a complex intervention to deliver better care were developed. Setting and Participants: Older people living with frailty, their informal carers and professionals living and/or working in West Yorkshire, England, UK. Deprescribing was considered in the context of primary care. Results: The current deprescribing process differed from an ideal pathway. A complex intervention containing seven elements was required to move towards the ideal pathway. Three of these elements were prototyped and four still need development. The complex intervention responded to priorities about (a) clarity for older people about what was happening at all stages in the deprescribing process and (b) the quality of one‐to‐one consultations. Conclusions: Priorities for improving the current deprescribing process were successfully identified. Solutions were developed and structured as a complex intervention. Further work is underway to (a) complete the prototyping of the intervention and (b) conduct feasibility testing. Patient or Public Contribution: Older people living with frailty (and their informal carers) have made a central contribution, as collaborators, to ensure that a complex intervention has the greatest possible potential to enhance the experience of deprescribing medicines.